Association between hashimoto thyroiditis and differentiated thyroid cancer: A single-center experience - Cappellacci, Federico; Canu, Gian Luigi; Lai, Maria Letizia; Lori, Eleonora; Biancu, Miriam; Boi, Francesco; Medas, Fabio (Frontiers in Oncology, 2022)
Hashimoto’s thyroiditis is the most common cause of hypothyroidism in the iodine-sufficient areas of the world. Differentiated thyroid cancer is the most common thyroid cancer subtype, accounting for more than 95% of cases, and it is considered a tumor with a good prognosis, although a certain number of patients experience a poor clinical outcome. Hashimoto’s thyroiditis has been found to coexist with differentiated thyroid cancer in surgical specimens, but the relationship between these two entities has not yet been clarified. Our study aims to analyze the relationship between these two diseases, highlighting the incidence of histological diagnosis of Hashimoto thyroiditis in differentiated thyroid cancer patients, and assess how this autoimmune disorder influences the risk of structural disease recurrence and recurrence rate.